Parkinson's disease and posture: evaluation with biometrical holistic of human body device: a pilot study - Ronconi, Gianpaolo; Ferrara, Paola E.; Codazza, Sefora; Gatto, Dario M.; La Cagnina, Fabiana; Coraci, Daniele; Panunzio, Maurizio; Ariani, Mariantonietta; Ferriero, Giorgio (Frontiers in Surgery, 2024)
Background: Patients with Parkinson’s disease (PD) commonly develop severe spinal deformity. The etiology of Parkinson’s spinal deformity is not completely understood and in most cases is likely due to multiple factors. These include dystonia and focal myopathy. Clinical, neurophysiological, and radiological data must be considered to monitor the pathology and the effects of rehabilitation. The aim of this pilot study is to evaluate spine alignment with a surface topography analysis of Parkinson’s patients with Biometrical Holistic of Human Body (BHOHB®) and to compare results with their X rays spine standard as already done for adolescent scoliosis. Methods: 32 adult patients affected by Parkinson disease, have been evaluated with BHOHB ®. The correspondence of the Cobb angles were evaluated using the BHOHB device and with standard spinal X rays. Results: A total of 32 patients were enrolled. The mean age was 67.45 years. In this pilot study the measurement of the correlations between the radiological and BHOHB® Cobb angles of the patients were excellent Conclusion: This preliminary result supports the use of BHOHB® as a device useful to monitor and measure posture in Parkinson’s. This needs to be evaluated on a larger sample and over time. Keywords: Parkinson’s disease, scoliosis, postural imbalance, neurophysiology.